Studies in Goethe's Lyric Cycles - Lee, Meredith (The University of North Carolina Press, 2021)
The book presents a series of interpretive readings of the "Römische Elegien", "Sonette", "Chinesisch-deutsche Jarhes- und Tageszeiten", several trilogies, and the shorter cycles of 1821, taking into account the variety of literary devices Goethe employs to link poems together into a cycle. The author examines Goethe's role in the history of the lyric cycle and, in stressing structural design, urges a reevaluation of the cycle's emergence as a standard poetic device.